2009
DOI: 10.1136/ard.2008.097212
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease in patients with ankylosing spondylitis

Abstract: The present study shows that patients with AS have a significantly higher risk of PD, strongly suggesting the need for close collaboration between rheumatologists, periodontists and dental hygienists when treating patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
7
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 29 publications
4
63
7
1
Order By: Relevance
“…A close association between inflammatory rheumatic diseases and infectious PD has been demonstrated in epidemiological studies [5][6][7][8]; however, limited data on pathomechanistic pathways exist [12][13][14]24,25,37]. Evidence of increased systemic bacteremia with oral pathogens has been observed in patients with inflammatory PD when compared with healthy controls [38].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A close association between inflammatory rheumatic diseases and infectious PD has been demonstrated in epidemiological studies [5][6][7][8]; however, limited data on pathomechanistic pathways exist [12][13][14]24,25,37]. Evidence of increased systemic bacteremia with oral pathogens has been observed in patients with inflammatory PD when compared with healthy controls [38].…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, epidemiologic studies point to an association between PD and inflammatory rheumatic diseases such as rheumatoid arthritis (RA) [4][5][6][7][8]. RA is a prevalent inflammatory disease of the world with a prevalence of 0.5-1.0% in Western populations [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Additional exclusion criteria included a history of diabetes or clinical inflammatory bowel disease. Sample size estimates for the CP prevalence as a primary outcome were derived based on the previously reported results by Pischon et al 10 (at an α error of 5% and statistical power of 95%): 35.4% of patients with AS and 12.5% of controls had CP with attachment loss (AL) >3.5 mm. The study was approved by the local ethical committee (Institutional Review Board Protocol B‐1206/156‐001), and written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, CP may provide a microbial reservoir affecting the development and clinical outcomes in AS. A few studies have investigated the association between AS and CP 10–12 . Two cross‐sectional studies reported contradictory results regarding the association between CP and AS 10 , 11 .…”
mentioning
confidence: 99%
“…Periodontitis is related to AS to a significant degree [4], and periodontitis is significantly more prevalent in patients with AS [5]. …”
Section: Introductionmentioning
confidence: 99%